Distribusi kecepatan arus pasang surut pada muson peralihan barat-timur terkait hasil tangkapan ikan pelagis kecil di perairan Spermonde - Abdul Rasyid Jalil (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2013)
Abstract. Indonesian waters connect the Pacific Ocean and the Indian Ocean. These waters are also highly influenced by the monsoonal climate. Current is a very important parameter in the marine environment and affect both directly and indirectly the marine environment. A study has been done in the waters of Spermonde Archipelago in Makassar Strait to develop a model of relationship between tidal current velocities and capture of small pelagic fishes at transition between west and east moonsoonal season. Insitu field data were collected for 3 (three) months, from April to June 2009. Besides that, this study also used a two-year image data (acquired from October 2007 to June 2009). Study sites were deployed in areas of fishing base of small pelagic fishes within the waters of Spermonde Archipelago, Pangkep District, South Sulawesi, particularly in areas where purse seine gears were operated by the fishermen. Distribution of current parameters, depth, wind direction and velocity, and tidal data were depicted horizontally using Surfer v 7.0 software package. Meanwhile, Surface Modelling System v 8.1. (SMS v 8.1) program was used to make prediction of the movement pattern of the surface current. Results of the analysis of current movement patterns when the waters were approaching hightide showed that water mass movement from southern region (Flores Sea) was diverted and passed through the Spermonde Archipelago to the coastline of Pangkep Regency. In contrary, when the waters were approaching ebb tide, the current from the western coast of Pangkep Regency passed the Spermonde Archipelago and diverted to the Flores Sea again. Analysis of current velocity indicated that higher current ( 0.1 m s-1) was found in offshore and tend to decrease below 0.1 m s-1 as the current passing the waters of Spermonde Archipelago. Optimal capture was obtained up to the current velocity of 0.032 m s-1 i.e. 187.9 kg, and tend to decrease with increasing current velocity. At the highest current velocity, that is 0.216 m s-1, the capture was 112 kg.